2023
DOI: 10.1177/13506501231163920
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis for offset-elliptical journal bearings under misalignment and dynamic loading

Abstract: Although the offset-elliptical journal bearings (OEJBs) are widely used in industry, there are few researches on the OEJBs, especially under the conditions of journal misalignment and sudden load. To overcome such deficiency, the dynamic response of misaligned OEJBs subjected to the dynamic load has been studied in this paper. Based on the Reynolds equation, Euler equation, and kinetic equations, a hydrodynamic model is developed and validated to conduct the transient analysis for the OEJBs. Moreover, the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. [8][9][10][11][12][13] As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. [14][15][16][17] In recent years, the numerical prediction of bearings during start-up has become increasingly sophisticated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. [8][9][10][11][12][13] As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. [14][15][16][17] In recent years, the numerical prediction of bearings during start-up has become increasingly sophisticated.…”
Section: Introductionmentioning
confidence: 99%
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. 813 As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. 1417…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Gu et al [28] developed a numerical model with misalignment and texture to analyze the axial trajectory and energy loss of bearings under time-varying dynamic load conditions. Wang et al [29] systematically studied the transient behavior of offset-elliptical bearing and found that the effect of misalignment on the minimum film thickness under dynamic load conditions is significant. Xiong et al [30] explored the impact of misalignment and viscoelastic deformation on the performance parameters and found that the coupling effects are more accurate under time-varying dynamic loads.…”
Section: Introductionmentioning
confidence: 99%